Hydrophobic association supramolecular gel suitable for oil and gas drilling in fractured formation - Han, Yongquan; Yu, Zhixue; Guan, Zijun; Ma, Rui; Hu, Yuzhou (Frontiers in Chemistry, 2024)
This paper presents a solution to drilling fluid leakage in gas formations with severe loss circulation during the oil and gas drilling. A supramolecular gel plugging agent, synthesized through micellar copolymerization based on hydrophobic binding, effectively seals cracks and pores in the formation during drilling operations. The agent is synthesized via free radical polymerization of monomers like acrylamide, methyl acrylate, and sodium dodecyl sulfate. Indoor evaluations assess the gelation time, viscoelastic properties, swelling behavior, mechanical properties, and plugging performance of the supramolecular gel, aligning with oil and gas drilling requirements.Results demonstrate controllable gelation time, good viscoelastic recovery with certain shear strain and scanning frequencies, and a compressive stress reaching 3.82 MPa at an 88.3% compression ratio. The supramolecular gel exhibits favorable swelling properties, with equilibrium swelling degrees of 22.1% after 188 min of swelling in a 15% NaCl solution and 32.5% in a 1% NaCl solution. In addition, it exhibits strong bonding capability and effective plugging performance, with over 95% plugging rate, reducing leakage and enhancing efficiency in mid and low-permeability layers. This study is significant for providing guidance on long-term plugging in non-homogenous formations with severe lost circulation issues.